New constraints on the relationship between 26Al and oxygen, calcium, and titanium isotopic variation in the early Solar System from a multielement isotopic study of spinel-hibonite inclusions. (1st July 2016) - Kööp, Levke; Nakashima, Daisuke; Heck, Philipp R.; Kita, Noriko T.; Tenner, Travis J.; Krot, Alexander N.; Nagashima, Kazuhide; Park, Changkun; Davis, Andrew M.
Abstract: We report oxygen, calcium, titanium and 26 Al– 26 Mg isotope systematics for spinel-hibonite inclusions (SHIBs), a class of calcium–aluminum-rich inclusions (CAI) common in CM chondrites. In contrast to previous studies, our analyses of 33 SHIBs and four SHIB-related objects obtained with high spatial resolution demonstrate that these CAIs have a uniform Δ 17 O value of approximately −23‰, similar to many other mineralogically pristine CAIs from unmetamorphosed chondrites (e.g., CR, CV, and Acfer 094). Five SHIBs studied for calcium and titanium isotopes have no resolvable anomalies beyond 3 σ uncertainties. This suggests that nucleosynthetic anomalies in the refractory elements had been significantly diluted in the environment where SHIBs with uniform Δ 17 O formed. We established internal 26 Al– 26 Mg isochrons for eight SHIBs and found that seven of these formed with uniformly high levels of 26 Al (a multi-CAI mineral isochron yields an initial 26 Al/ 27 Al ratio of ∼4.8 × 10 −5 ), but one SHIB has a smaller initial 26 Al/ 27 Al of ∼ 2.5 × 10 −5, indicating variation in 26 Al/ 27 Al ratios when SHIBs formed. The uniform calcium, titanium and oxygen isotopic characteristics found in SHIBs with both high and low initial 26 Al/ 27 Al ratios allow for two interpretations. (1) If subcanonical initial 26 Al/ 27 Al ratios in SHIBs are due to early formation, as suggested by Liu et al. (2012), our data would indicate that the CAI formation region had achieved a high degree of isotopic homogeneity in oxygen and refractory elements before a homogeneous distribution of 26 Al was achieved. (2) Alternatively, if subcanonical ratios were the result of 26 Al– 26 Mg system resetting, the clustering of SHIBs at a Δ 17 O value of ∼−23‰ would imply that a 16 O-rich gaseous reservoir existed in the nebula until at least ∼0.7 Ma after the formation of the majority of CAIs.